2014
DOI: 10.1155/2014/197824
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Photocatalytic Activity of Zn-Doped SnO2/Zn2SnO4Coupled Nanocomposites

Abstract: Zn-doped SnO2/Zn2SnO4nanocomposites were prepared via a two-step hydrothermal synthesis method. The as-prepared samples were characterized by X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), UV-vis diffuse reflection spectroscopy, and adsorption-desorption isotherms. The results of FESEM and TEM showed that the as-prepared Zn-doped SnO2/Zn2SnO4nanocomposites are composed of numerous nanoparticles with the size ranging from 20 nm to 50 nm. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…It was therefore concluded that the higher photocatalytic activity of ZnFe 2 O 4 /ZnO nanopowder is due to an increase in the electron hole separation. This type of interparticle charge transfer (synergistic mechanism) has also been reported in case of other nanocomposites such as SnO 2 /Zn 2 SnO 4 and TiO 2 /SnO 2 [58,59].…”
Section: Resultssupporting
confidence: 74%
“…It was therefore concluded that the higher photocatalytic activity of ZnFe 2 O 4 /ZnO nanopowder is due to an increase in the electron hole separation. This type of interparticle charge transfer (synergistic mechanism) has also been reported in case of other nanocomposites such as SnO 2 /Zn 2 SnO 4 and TiO 2 /SnO 2 [58,59].…”
Section: Resultssupporting
confidence: 74%
“…10b)of the SZTO composite can be constructed based on the information of Efb and Eg of SnO2 and ZTO.Apparently, the Ecb of SnO2 is more negative than that of ZTO, while the valence band top potential (Evb) of ZTO is more positive than that of SnO2. Similar band structure of SZTO composite has been proposed[34,35]. Thus, a type−II heterojunction can be expected.…”
supporting
confidence: 76%
“…This strategy is more effective than the doping process to improve the photocatalytic performance as the formation of mid−gap or vacancy states can be largely avoided. The literatures indicated that ZTO could be coupled with WO3, Fe2O3, ZnO, SnO2, g−C3N4, and BiOI and the resulted composites showed enhanced sensor, electrical, or photovoltaic responses [9,13,31−36], as well as the photocatalytic activity [13,30,34,35]. Moreover, the activity could be even extended to the visible light region by coupling with some narrow bandgap semiconductors like g−C3N4 and BiOI [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The similar XRD patterns of samples indicates that ZnO doping only filled into the lattice of SnO 2 with the form of displacement, instead of changing the rutile structure of SnO 2 [13] . The diffraction intensity increases when the doping quantity of ZnO is 0.5wt.% and 0.7 wt.%, which is because the generated Zn 2 SnO 4 [14] filled the gap of SnO 2 lattice, promoting the sintering densification of tin oxide ceramics. Figure 2 shows that the samples' porosity is significantly increased when the doping quantity of ZnO is 0.1wt.%.…”
Section: Sample Characterizationmentioning
confidence: 99%